Sketching the investigative trends of research articles on the deployment of English for accounting: a scientometric study - Irman Firmansyah; Fuad Abdullah (Institute of Advanced Engineering and Science, 2024)
This study scientometrically mapped the investigative trends in English for accounting (EA) research articles. The corpus was 181 research articles in EA from 1981 to 2021. They were retrieved from metadata dimensions of various leading journals and analyzed with automated bibliometric analysis. The findings revealed that the investigative themes in EA remain burgeoning for 41 years. The accounting history journal indicated the greatest impact on EA research. The analyzed journals reported a large impact correlating to their development. The most productive author in the EA research was Jones. The typical words frequently emerging in the analyzed research articles were accounting, research, and English. The investigative and developing topics related to EA were relatively dynamic. This study suggests that the scientometric investigative perspective offers a systematic, diachronic, and quantitative outline of English for accounting research by considering its meta-disciplinary knowledge and evolving trends over the years.